2005
DOI: 10.1097/01.smj.0000157537.11806.dc
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case of Fatal Yellow Fever Vaccine-associated Viscerotropic Disease

Abstract: The live, attenuated 17D vaccine against yellow fever has been used effectively as a vaccine for more than 50 years. Yellow fever was the third human disease to be controlled by vaccination, after smallpox and rabies.2 Currently, the yellow fever vaccine is manufactured by six World Health Organization-approved institutes worldwide. 2 The yellow fever vaccine is used as a routine immunization for infants in many countries, and a valid certificate of vaccination is required for travelers to enter 127 countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…However, a few YFV-AND cases have been fatal with virus recovered from brain tissues and the YFV-17D genome detected in the cerebral spinal fluid (Anonymous,1966;Kengsakul et al, 2002;Monath et al, 2013). The pathogenesis of YFV-AVD is similar to severe WT YFV infection with high case-fatality rates characterized by viral replication in numerous visceral tissues and liver histopathology (Belsher et al, 2007;Centers for Disease Control and Prevention, 2002;Cetron et al, 2002;Chan et al, 2001;Gerasimon & Lowry, 2005;Martin et al, 2001;Monath et al, 2013;Vasconcelos et al, 2001). Evaluation of the immune response in a few cases of YFV-17D-associated adverse events found elevated levels of liver enzymes and cytokines similar to WT YFV infection (Bae et al, 2008;Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few YFV-AND cases have been fatal with virus recovered from brain tissues and the YFV-17D genome detected in the cerebral spinal fluid (Anonymous,1966;Kengsakul et al, 2002;Monath et al, 2013). The pathogenesis of YFV-AVD is similar to severe WT YFV infection with high case-fatality rates characterized by viral replication in numerous visceral tissues and liver histopathology (Belsher et al, 2007;Centers for Disease Control and Prevention, 2002;Cetron et al, 2002;Chan et al, 2001;Gerasimon & Lowry, 2005;Martin et al, 2001;Monath et al, 2013;Vasconcelos et al, 2001). Evaluation of the immune response in a few cases of YFV-17D-associated adverse events found elevated levels of liver enzymes and cytokines similar to WT YFV infection (Bae et al, 2008;Silva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the cases have been detailed in the literature: Doblas et al (2006) reported the death of a 26-year-old woman who was vaccinated for YF, diphtheria, and tetanus; Zhou et al (2005) reported a 60-year-old man who had chemotherapy for rectal cancer and was vaccinated against YF and meningococcus, and survived; Gerasimon and Lowry (2005) reported the death of a 22-year-old woman who was vaccinated against YF and influenza; and Kitchener (2004) retrospectively found four cases of YEL-AVD where all of the people had received concurrent tetanus toxoid (either combined or singular formulation) vaccination. The most recent cases are a cluster of four fatal cases in Peru from a total of 42,000 given the same lot of vaccine.…”
Section: Yellow Fever Vaccine -Associated Neurotropicmentioning
confidence: 98%
“…19 YEL-AND typically occurs in first-time vaccines, approximately two to 30 days post vaccination, and carries a case fatality rate of below five per cent. Between 1990-2004, 11 cases of YEL-AND were identified among US citizens.…”
Section: Yellow Fever Neurotropic Diseasementioning
confidence: 99%